eCM 2010
DOI: 10.22203/ecm.v020a12
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen-hyaluronan hydrogel – a step towards a scaffold for intervertebral disc tissue engineering

Abstract: Intervertebral disc regeneration strategies based on stem cell differentiation in combination with the design of functional scaffolds is an attractive approach towards repairing/regenerating the nucleus pulposus. The specific aim of this study was to optimise a composite hydrogel composed of type II collagen and hyaluronic acid (HA) as a carrier for mesenchymal stem cells. Hydrogel stabilisation was achieved by means of 1-ethyl-3(3-dimethyl aminopropyl) carbodiimide (EDC) and Nhydroxysuccinimide (NHS) cross-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 66 publications
4
117
0
Order By: Relevance
“…Hence, these are frequently included in possible tissue engineering treatment approaches (Priyadarshani et al, 2015), e.g. agarose (Awad et al, 2004;Bougault et al, 2012;Iwata et al, 2013;Luo et al, 2015;Mauck et al, 2006), collagen (Borde et al, 2015;Calderon et al, 2010;Mercuri et al, 2014;Omlor et al, 2012;Tsaryk et al, 2015), alginate (Bron et al, 2011;Duggal et al, 2009;Xu et al, 2008;Zeng et al, 2015a), chitosan (Naqvi and Buckley, 2015;Ngoenkam et al, 2010), and combinations of alginate and chitosan have been investigated (Shao , 2007). Although natural hydrogels generally offer good cytocompatibility, they often possess inferior mechanical properties (Schutgens et al, 2015).…”
Section: Reinforced Hydrogels For Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…Hence, these are frequently included in possible tissue engineering treatment approaches (Priyadarshani et al, 2015), e.g. agarose (Awad et al, 2004;Bougault et al, 2012;Iwata et al, 2013;Luo et al, 2015;Mauck et al, 2006), collagen (Borde et al, 2015;Calderon et al, 2010;Mercuri et al, 2014;Omlor et al, 2012;Tsaryk et al, 2015), alginate (Bron et al, 2011;Duggal et al, 2009;Xu et al, 2008;Zeng et al, 2015a), chitosan (Naqvi and Buckley, 2015;Ngoenkam et al, 2010), and combinations of alginate and chitosan have been investigated (Shao , 2007). Although natural hydrogels generally offer good cytocompatibility, they often possess inferior mechanical properties (Schutgens et al, 2015).…”
Section: Reinforced Hydrogels For Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…Traditionally the biocompatability of natural polymer scafolds has been an appealing choice for NP repair, including collagen [121], alginate [65], gelatine [60], hylauronan [67,68], chitosan-glycerophosphate [94,107] and thermoresponsive hyaluronic acid (Table 1) [71]. However the use of natural polymers raises concerns regarding batch variation and immunogenic risk; consequently a number of studies have looked to develop synthetic polymer scafolds which have the added advantage of synthesis control, large scale production and the ability to tailor bioactivity, mechanical properties and degradation rates.…”
Section: Cellular Biomaterials For Disc Degenerationmentioning
confidence: 99%
“…The degradation dynamics of Gel/HA hydrogels was studied by enzymatic degradation with a 10 U/ml solution of hyaluronidase and 3 U/mL of collagenase in DPBS, these concentrations being within the range typically used in the bibliography [90], [91], [114], [131], [225], [226]. A mixture of both enzymes was used to study degradation, since it has been demonstrated that the combination of both produces higher degradation rates than when only one is used [69].…”
Section: Enzymatic Degradation Of Gel/ha Hydrogelsmentioning
confidence: 99%